AYAT TOLERANSI DALAM AL-QURâ€™AN: Tinjauan Tafsir Marah Labid - Baharudin Zamawi; Habieb Bullah; Zubaidah Zubaidah (UIN Siber Syekh Nurjati Cirebon, 2019)
The nation of Indonesia is one country that has a diversity of abundant, better than tribe, language, or Religion., in the context of this community demanded to apply the meaning of tolerance, in order to realize a pluralistic nation, in accordance with the motto which is sturdy in Indonesia is Bhinneka tunggal Ika which means â€œDifferent but still oneâ€. However at this time very much the presence of various conflicts among the religious, so that in reality a religion that teaches to love each other no longer be the role of in peace and harmony, Indonesian society is multi cultural has a face the paradox of change. Islam is the religion of the majority in the community believe Indonesia, therefore, in the development of attitudes and the nature, muslims must demonstrate the value of tolerant to the society, in the religion of Islam Alquran as a book of guidance for muslims, Alquran has explained or has given way for the people of Islam in solving a problem which on the whole concerns the relationship of the social good on a community or personal. that is the reality that in many communities embraced different religions. The religion of Islam trying to dig up the Islamic concept of tolerance that is being obscured its meaning, especially to the younger generation. In a context like this, then we will study the Tafsir of the verses of the holy Quran version Tafsi>r Marah Labi>d by Shaykh Muhammad Al-Nawawi Al-Jawi.